Strategi Public Relations dalam Mempertahankan Citra Positif: Studi Kasus RRI Bandung - Annisa Oktaviani Dewi; Maman Suherman (Bandung Conference Series: Public Relations, 2022)
Abstract. Various kinds of Private Radio Competitors made RRI Radio Government devise a strategy to maintain its image so that it remains the leading one. The many public stigmas regarding RRI's image seemingly old-fashioned and left behind give researchers a deep sense of curiosity about the strategies used by RRI Bandung PR. Therefore, the author conducted a study entitled "RRI Bandung PR Strategy in Maintaining a Positive Image (Case Study at LPP RRI Bandung)." The purpose of this study is to find out attempt the strategies used in following the development of radio, improving radio quality, improving radio imagery from internal pr, and improving radio imagery from external pr. The research uses Image Theory with Qualitative Methods using Qualitative Data Analysis Techniques where in the data collection using Literature Studies, Field Observations, Interviews and Literature. RRI Bandung has two factors that affect the image, namely, Internal and External. Internally through the views of employees while External is through listeners of RRI Bandung according to the Informant of the Head of Broadcasting. Based on the results of the interview, the PR Strategy carried out has been running well but is still not optimal in the public relations section of lpp held by the Head of LPU. The type of image taken is the image of Frank Jefkins in the form of Characters from each Program, Segmentation, Image Branding and Marketing using the concept strategy of rosady Ruslan Strategy. Abstrak. Berbagai macam Kompetitor Radio Swasta membuat RRI Radio Pemerintah menyusun strategi mempertahankan citra agar tetap menjadi yang terunggul. Banyaknya stigma masyarakat mengenai citra RRI terkesan kuno dan tertinggal memberi rasa keingintahuan yang mendalam bagi peneliti mengenai strategi yang digunakan oleh PR RRI Bandung. Oleh karena itu, penulis mengadakan penelitian yang berjudul “Strategi PR RRI Bandung Dalam Mempertahankan Citra Positif (Studi Kasus di LPP RRI Bandung).” Tujuan dalam penelitian ini untuk mengetahui Bagaimana upaya yang digunakan dalam mengikuti perkembangan radio, meningkatkan mutu radio, meningkatkan citra radio dari pr internal, dan meningkatkan citra radio dari pr eksternal . Penelitian menggunakan Teori Citra dengan Metode Kualitatif memakai Teknik Analisis Data Kualitatif dimana dalam pengumpulan datanya menggunakan Studi Kepustakaan, Observasi Lapangan , Interview dan Literature. RRI Bandung memiliki dua faktor yang mempengaruhi citra yakni, Internal dan Eksternal. Internalnya melalui pandangan karyawan sedangkan Externalnya melalui pendengar RRI Bandung menurut Informan Ketua Bidang Siaran. Berdasarkan hasil wawancara bahwa Strategy PR yang dilakukan sudah berjalan dengan baik namun masih belum maksimal di humas bagian LPP yang dipegang oleh Ketua Bidang LPU. Jenis citra yang diambil adalah Citra dari Frank Jefkins berupa Karakter dari setiap Program,Segmentasi, Image Branding dan Marketing dengan memakai strategi konsep dari Strategi Rosady Ruslan.